Search for the decay of a Higgs boson in the ℓℓγ channel in proton-proton collisions at √s = 13 TeV - Sirunyan, A. M. (2018)
A search for a Higgs boson decaying into a pair of electrons or muons and a photon is described. Higgs boson decays to a Z boson and a photon (H ! Z ! `` ,` = e or ), or to two photons, one of which has an internal conversion into a muon pair (H ! ! ) were considered. The analysis is performed using a data set recorded by the CMS experiment at the LHC from proton-proton collisions at a center-of-mass energy of 13TeV, corresponding to an integrated luminosity of 35.9 fb1. No signi cant excess above the background prediction has been found. Limits are set on the cross section for a standard model Higgs boson decaying to opposite-sign electron or muon pairs and a photon. The observed limits on cross section times the corresponding branching fractions vary between 1.4 and 4.0 (6.1 and 11.4) times the standard model cross section for H ! ! (H ! Z ! `` ) in the 120{130 GeV mass range of the `` system. The H ! ! and H ! Z ! `` analyses are combined for mH = 125 GeV, obtaining an observed (expected) 95% con dence level upper limit of 3.9 (2.0) times the standard model cross section.